Use of ants foraging behaviour for routing in ad hoc networks. (2018) - Reddy, P. Chenna
The heterogeneous nature of computer networks and widely varying application requirements pose many challenges to the designers of the protocols. This paper classifies the challenging issues of a computer network into expected, demanding and future requirements. Biological solutions can be used to solve computer networks related problems. This paper maps the challenging issues of computer networks to the corresponding solutions of biological systems. It classifies the biological solutions based on application category. This paper identifies the parallels between self-organisation and ad hoc networks giving the justification for using self-organisation in ad hoc networks. This paper illustrates how foraging behaviour of ants can be used to solve the routing problem in ad hoc networks, and critically analyses ants foraging to find the limitations of it. It identifies the scope for improvement of the existing methods for routing and also suggests ways of improving based on ants foraging behaviour.